2021
DOI: 10.3390/jcdd8060063
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Lipoprotein(a) and Circulating Monocyte Subsets with Severe Coronary Atherosclerosis

Abstract: Background and aims: Chronic inflammation associated with the uncontrolled activation of innate and acquired immunity plays a fundamental role in all stages of atherogenesis. Monocytes are a heterogeneous population and each subset contributes differently to the inflammatory process. A high level of lipoprotein(a) (Lp(a)) is a proven cardiovascular risk factor. The aim of the study was to investigate the association between the increased concentration of Lp(a) and monocyte subpopulations in patients with a dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…The activation of the innate immune system in patients with hyperlipoproteinemia(a) is consistent with our recent study, which demonstrated that in patients with an elevated Lp(a) concentration, there is a redistribution of monocyte subpopulations towards an increase in CD14+CD16++ monocytes [13]. Furthermore, the combination of hyperlipoproteinemia(a) and a higher content of intermediate monocytes was associated with a significant increase in stenotic plaques in all major coronary arteries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The activation of the innate immune system in patients with hyperlipoproteinemia(a) is consistent with our recent study, which demonstrated that in patients with an elevated Lp(a) concentration, there is a redistribution of monocyte subpopulations towards an increase in CD14+CD16++ monocytes [13]. Furthermore, the combination of hyperlipoproteinemia(a) and a higher content of intermediate monocytes was associated with a significant increase in stenotic plaques in all major coronary arteries.…”
Section: Discussionsupporting
confidence: 90%
“…There are data that Lp(a) is able to enhance the production of inflammatory monocytes in the bone marrow [12]. We have recently shown that in patients with an elevated Lp(a) level, the absolute and relative content of non-classical CD14+CD16++ monocytes is significantly higher [13], indicating the ability of Lp(a) to influence monocytes. Residual cardiovascular risk in patients with atherosclerosis, despite adequate hypolipidemic therapy, could be related to the increased concentration of Lp(a) and, therefore, the possible relationship between Lp(a) and the vascular wall inflammation deserves further evaluation.…”
Section: Introductionmentioning
confidence: 92%
“…Patients with atherosclerosis in multiple vessels had significantly more CD16+ (intermediate + nonclassical) monocytes than those with single vessel disease [24]. This relationship was also seen when patients were divided by proportion of monocyte subsets, with those below median for classicals or above median for intermediate or nonclassicals having a higher occurrence of multivessel disease [25]. In PAD patients, the presence of ischemic ulcer (an indicator of greater disease severity) is associated with decreases in classical monocyte proportion and increases in intermediate monocyte proportion [26].…”
Section: Monocyte Subset Proportions In Cvdmentioning
confidence: 80%
“…Whereas the development of CAD is a dynamic process [1], little attention has been paid to the changes in Lp(a) levels at different times. One study showed that elevated Lp(a) levels were associated with CD14, CD16 monocyte reduction and coronary atherosclerosis, but the study inclusion population did not include patients with coronary events [12]. In the last decades, coronary heart disease remains the leading cause of death worldwide [13].…”
Section: Discussionmentioning
confidence: 99%